Advances in Composite Materials Development - Lucan, Dumitra (IntechOpen, 2019)
The progress of technology is a permanent challenge in developing new materials with superior properties in terms of quality and reliability. The demand for increased performance continues to focus materials development efforts on exploring new concepts or new generations of composite materials. The chapters contained in this book represent many examples of research results dedicated to obtaining, characterizing, and mathematically modeling composite materials, especially metal matrix composites, with superior properties having a wide range of applications. The book is addressed to researchers and materials specialists, teachers and students at science and material engineering faculties, and all those interested in advances in science and technology of new materials.